The Effect of Family History of Hypertension, Dietary Patterns, and Smoking History on Hypertension among Older Adults in the Working Area of Kisol Community Health Center, East Manggarai - Elperona, Bentina A.; Oematan, Grouse (Jurnal Pangan Gizi dan Kesehatan, 2026)
Background: Hypertension is one of the major health problems in the elderly that increases the risk of cardiovascular disease and mortality. Objectives :This study aims to analyze the effect of family history of hypertension, dietary patterns, and smoking history on the incidence of hypertension in the elderly in the working area of the Kisol Community Health Center, East Manggarai Regency. This study used a quantitative approach with a case-control design. The study sample consisted of 161 elderly respondents aged ≥60 years, determined using the Slovin formula through random sampling. Method: Data were collected using questionnaires, interviews, and blood pressure measurements, then analyzed using the chi-square test at a significance level of 5%. Results: The results showed a significant association between family history of hypertension and the incidence of hypertension (p=0.000) as well as dietary patterns and the incidence of hypertension (p=0.000). Conversely, smoking history was not significantly associated with the incidence of hypertension (p=0.287). It is recommended that the Community Health Center strengthen nutrition education and routine screening.